O cotidiano de quem vive a realidade da fome: práticas alimentares e estratégias de acesso aos alimentos - Blümke, Adriane Cervi (Universidade do Vale do Rio dos Sinos, 2017)
The objective of this study was to understand the hunger phenomenom from the perspective of social actors that experience it in their everyday lives. We started from the assumption that hunger, conceived by Josué de Castro, is still one of the greatest social dilemmas in Brazil and a condition of iniquity in a context of deprivation of human capabilities, as John Rawls and Amartya Sen suggest. The food besides being a human right is also a daily act permeated by the culture that, in the urban is influenced by a series of factors. A social anthropological study was conducted of February to May 2016 with families that experience hunger on a daily basis, in the Alto da Boa Vista community, located in the Nova Santa Marta neighborhood in the city of Santa Maria, RS. We used script-guided interviews and field notes on daily, being the analytical process was conducted through the Content Analysis technique proposed by Laurence. The major findings show that the hunger experienced and felt slowly corrodes the individuals' body and soul, it is consequence of a body expression of the quantitative physiological need of food that causes a feeling of emptiness and physical pain, it generates a feeling of incapacity, it causes sadness and great concern about the uncertainty of tomorrow. Another find is the habitus shortage due to the precariousness of food, the restrict number of meals and the absence of breakfast caused by the lack of bread. The families develop dietary adjustments to live with the hunger, such as practicing the brunch or lunch/afternoon snack, drinking water or "chimarrão" tea when they are hungry, eating less so that there is food left for the next meal or for the children. Among the strategies of access, the most identified was the solidarity with the establishment of a support network and food aid from friends, neighbors and relatives. It is necessary to increase our analysis capacity in relation to the hunger problem as well as, public policies food and nutrition and food and nutrition safety which have a limited scope for families that really need a speech that privileges the neoliberal policies to the detriment of equitable access to food, which continues to be a big ethical, political and economic challenge to be faced.
Keywords: Fome; Alimentação; Equidade; Políticas públicas; Segurança alimentar e nutricional; Hunger; Equity; Public policies; Food and nutrition security; ACCNPQ::Ciências Humanas::Sociologia